ADOMAIN DECOMPOSITION METHOD FOR SOLVING SYSTEMS OF MULTI-DIMENSIONAL LINEAR FREDHOLM INTEGRAL EQUATIONS OF THE SECOND KIND - Khaleel, Ahlam Jameel; Hasoon, Hanan Mahmood (Al-Nahrain Journal of Science, 2010)
The aim of this work is to use Adomian decomposition method to solve Systems of multidimensionallinear Fredholm integral equations of the second kind